Penyuluhan Bahaya Asap Rokok Pada Ibu Hamil di Posyandu Mawar Puskesmas Karangrejo, Kota Metro - Elisa Murti Puspitaningrum; Firda Fibrila; Gangsar Indah Lestari (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2025)
Cigarette smoke is a mixture of smoke and particles. The smoke consists of 4000 mixed chemical compounds, including toxic substances and 69 of them are cancer-causing substances. Pregnant women who are exposed to cigarette smoke will have an impact on their pregnancy and fetus, such as low birth weight, risk of premature birth, respiratory problems and other fetal development disorders. This community service activity is to increase pregnant women's knowledge about the dangers of cigarette smoke during pregnancy. The method of this activity is to provide direct counseling to 20 pregnant women. It is hoped that pregnant women can avoid exposure to cigarette smoke around them so that it does not harm the health of the fetus during pregnancy.